2015
DOI: 10.1038/ncomms9776
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput 3D tracking of bacteria on a standard phase contrast microscope

Abstract: Bacteria employ diverse motility patterns in traversing complex three-dimensional (3D) natural habitats. 2D microscopy misses crucial features of 3D behaviour, but the applicability of existing 3D tracking techniques is constrained by their performance or ease of use. Here we present a simple, broadly applicable, high-throughput 3D bacterial tracking method for use in standard phase contrast microscopy. Bacteria are localized at micron-scale resolution over a range of 350 × 300 × 200 μm by maximizing image cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
190
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(199 citation statements)
references
References 43 publications
9
190
0
Order By: Relevance
“…All crossing events were inspected manually to prevent this. To identify runs and tumbles, we utilized a method based on reference (Taute et al, 2015) which was modified from the approach used by Berg and Brown (1972). Briefly, for each cell the segmentation routine results in a matrix of spatial locations xfalse→false(tfalse).…”
Section: Materials and Methodsmentioning
confidence: 99%
“…All crossing events were inspected manually to prevent this. To identify runs and tumbles, we utilized a method based on reference (Taute et al, 2015) which was modified from the approach used by Berg and Brown (1972). Briefly, for each cell the segmentation routine results in a matrix of spatial locations xfalse→false(tfalse).…”
Section: Materials and Methodsmentioning
confidence: 99%
“…As a consequence of the steady improvement of the spatiotemporal resolution of microscopic techniques, advances in automated particle tracking and motion analysis Arhel et al, 2006;Jaqaman et al, 2008;Chenouard et al, 2014;Smith et al, 2015;Genovesio et al, 2006), and the availability of software tools Schindelin et al, 2012;de Chaumont et al, 2012;Eliceiri et al, 2012;Perry et al, 2012;Swedlow and Eliceiri, 2009;Tinevez et al, 2016;Jaqaman et al, 2008;Kalaidzidis, 2009;Incardona and Sbalzarini, 2014), SPT holds the promise of becoming amenable to multidimensional high-throughput data collection schemas (Damm and Pelkmans, 2006;Snijder et al, 2012;Rämö et al, 2014;Taute et al, 2015).…”
Section: Description Of the Problemmentioning
confidence: 99%
“…Moreover, recent work has shown that it is possible to use comparisons of observed diffraction patterns with reference libraries to perform high-throughput tracking of swimming bacteria in 3D without specialized instrumentation. 34 Multiimaging modalities have proven valuable not only in the medical field, e.g. , PET-CT, but also in cellular microscopy.…”
mentioning
confidence: 99%